The effects of fragmentation on the genetic structure of Theobroma speciosum (Malvaceae) populations in Mato Grosso, Brazil - Dardengo, Juliana de Freitas Encinas (2018)
Native Theobroma species, such as cacauhy, are losing their habitat due to the intense forest fragmentation in the Amazon region, and preserving their genetic diversity has been the main aim of many conservation programs. The aim of the present study is to assess whether fragmentation and habitat reduction affect the genetic structure and lead to genetic diversity losses in natural Theobroma speciosum populations. The study was conducted in two Mato Grosso State (Brazil) locations, namely: Apiacás and Alta Floresta counties. Juruena National Park (JNP) in Apiacás County holds a natural T. speciosum population that has not underwent anthropic influences. A population composed of individuals from three anthropized urban forest parks (UF) in Alta Floresta County was analyzed. The leaves of 75 T. speciosum individuals distributed in the urban forest fragments and of 100 individuals found in the Juruena National Park were sampled. All nine microsatellite loci showed high polymorphism levels between categories (adults and sub-adults), in both populations. The sub-adult individuals of the population (UF) in the fragmented area showed higher value (0.71), whereas the preserved population (JNP) category presented the same value (0.69). The increasing trend of estimating the fixation index towards the fragmented population was observed. The analysis of molecular variance showed 83 % genetic diversity within categories; 16 %, between populations; and only 1 %, between categories. Although the effects were small, a persistent fragmentation process can increase the inbreeding levels and facilitate the genetic drift action. These effects may lead the T. speciosum populations to inbreeding depression, diversity loss and genetic structure change in the course of several generations.